2021
DOI: 10.1097/brs.0000000000004092
|View full text |Cite
|
Sign up to set email alerts
|

PROMIS Scores Should Not be Used in Isolation to Measure Outcomes in Lumbar Stenosis Patients

Abstract: Study Design. Retrospective cross-sectional analysis.Objective. The aim of this study was to establish the strength of relationship between the Patient-reported Outcomes Measurement Information System (PROMIS) Adult Depression (AD), Physical Function (PF), and Pain Interference (PI) with the Swiss Spinal Stenosis Questionnaire (SSSQ) in assessing lumbar spinal stenosis (LSS). Summary of Background Data. In 2009, there were >35,000 surgeries for LSS, which amounted to $1.65 billion in health care cost. By 2021,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…Similarly, in lumbar spinal stenosis patients, Patel et al demonstrated the efficiency, convergent and discriminatory validity, and responsiveness of PROMIS CATs compared with legacy measures 42 . Although the PROMIS CAT was deemed valid based on its comparison with the aforementioned legacy measures, a subsequent study 44 assessed PROMIS CAT using the Swiss Spinal Stenosis Questionnaire (SSSQ), which has been recommended by the North American Spine Society as the “criterion standard” for LSS outcomes 45 . The authors concluded that PROMIS should not be used in isolation to evaluate patients with lumbar spinal stenosis because there were poor correlations with these legacy instruments.…”
Section: Promis Validation and Comparisons In Specific Lumbar Spine C...mentioning
confidence: 99%
“…Similarly, in lumbar spinal stenosis patients, Patel et al demonstrated the efficiency, convergent and discriminatory validity, and responsiveness of PROMIS CATs compared with legacy measures 42 . Although the PROMIS CAT was deemed valid based on its comparison with the aforementioned legacy measures, a subsequent study 44 assessed PROMIS CAT using the Swiss Spinal Stenosis Questionnaire (SSSQ), which has been recommended by the North American Spine Society as the “criterion standard” for LSS outcomes 45 . The authors concluded that PROMIS should not be used in isolation to evaluate patients with lumbar spinal stenosis because there were poor correlations with these legacy instruments.…”
Section: Promis Validation and Comparisons In Specific Lumbar Spine C...mentioning
confidence: 99%
“…Specifically, analyses show a low correlation coefficient ( R value) (indicating the relationship is relatively weak) with a significant P value (indicating a high probability that the association is not due to chance) [32]. This issue is becoming increasingly relevant as comprehensive assessments, such as those measuring the impact of a given condition on overall health and well-being, are considered indicators of the quality of health care [19,33]. Such health indicators are important to patients, stakeholders, and administrators.…”
Section: Introductionmentioning
confidence: 99%